Improved calcium sensor GCaMP-X overcomes the calcium channel perturbations induced by the calmodulin in GCaMP - Yaxiong Yang (Nature Portfolio, 2018)
The popular genetically-encoded Ca2+ indicator, GCaMP, has several side-effects. Here the authors show that GCaMP containing CaM interferes with gating and signaling of L-type calcium channels, which disrupts Ca2+ dynamics and gene expression, and develop GCaMP-X to overcome these limitations.